(untitled) (Journal of Management and Social Sciences, 2017)
Abstract The desired goal(s) of any democratic experiment the world over is to make life comfortable for the generality of the citizenry through provision of food, adequate shelter, habitable housing, functional and free education, avoidable and accessible health care system, functional public/social infrastructures among others. The realization of these democratic dividends since the return of the country to democraticrule in 1999 is dampened by the existence of wide spread poverty among the citizens.Poverty has seriously impacted on the democratic process in such a way that the type of leadership that have emerged in the present republic were not people friendly as they lack patriotism, sincerity, management skills, vision, morality and political will to put in place necessary programmes that will ameliorate the already worsening situation of the masses. This paper examines the diverse ways through which poverty has negatively influence our democratic process. It argues that no meaningful dividends of democracy will come out of the present experiment until the issues underlying the continue slavery of the people are addressed. Possible suggestions to ameliorate the poverty induced pathetic conditions of the masses are suggested, these include: the need on the various tiers of government to redistribute the revenue of the state in way that benefit lower income groups; government should support hospital and schools; give aids to the families to reduces the risk of crime and political conflict since poorer families are likely to seek illegal means of earning income or to unite in protest over their living conditions; there is need to fight the menace of corruption through control mechanism, provision of job- training and job - search programmes for adults and compensatory education programmes for the children so they are better able to find well-paying job. There is serious need to change the way we do things so as to benefit the poor through altering the tax system; encouraging the creation of good jobs, reducing discrimination, and the like. Keywords Poverty, democracy, dividends of democracy, leadership, corrupt practices, electoral process